2017
DOI: 10.1017/jfm.2017.370
|View full text |Cite
|
Sign up to set email alerts
|

Shear-induced incipient motion of a single sphere on uniform substrates at low particle Reynolds numbers

Abstract: We study the incipient motion of single spheres in steady shear flow on regular substrates at low particle Reynolds numbers. The substrate consists of a monolayer of regularly arranged fixed beads, in which the spacing between beads is varied resulting in different angles of repose and exposures of the particle to the main flow. The flow-induced forces and the level of flow penetration into the substrate are determined numerically. Since experiments in this range had shown that the critical Shields number is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(54 citation statements)
references
References 80 publications
5
49
0
Order By: Relevance
“…The AOR of granular material is the inclination angle relative to the horizontal plane when the particle is at static condition. At this angle, the material on the slope is at the edge of sliding 39 . Generally, the decrease of AOR is indicative of improved fluidization characteristics of particles.…”
Section: Resultsmentioning
confidence: 99%
“…The AOR of granular material is the inclination angle relative to the horizontal plane when the particle is at static condition. At this angle, the material on the slope is at the edge of sliding 39 . Generally, the decrease of AOR is indicative of improved fluidization characteristics of particles.…”
Section: Resultsmentioning
confidence: 99%
“…It is also not equivalent to the comparably simple physics of fluid entrainment by a nonfluctuating flow. For example, when a laminar flow of a Newtonian fluid shears a target particle resting on the sediment bed, there are critical values of the fluid shear stress τ, which depend on the local bed arrangement, above which this particle begins to roll and slide, respectively (Agudo et al, ; Deskos and Diplas, ). Once motion begins, resisting forces weaken and, since the flow does not fluctuate, the particle will inevitably leave its bed pocket (i.e., become entrained).…”
Section: Fluid Entrainment By Turbulent Flowsmentioning
confidence: 99%
“…Mean flow entrainment models derive a transport initiation threshold Shields number from a force balance, and/or torque balance, between mean fluid forces and resisting contact forces acting on a representative particle resting on the bed surface (Agudo et al, 2017;Ali & Dey, 2016;Bagnold, 1936Bagnold, , 1941Bravo et al, 2014Bravo et al, , 2017Claudin & Andreotti, 2006;Dey, 1999Dey, , 2003Dey & Papanicolaou, 2008;Duan et al, 2013;Durán et al, 2011;Edwards & Namikas, 2015;He & Ohara, 2017;Iversen et al, 1976Iversen et al, , 1987Iversen & White, 1982;Lee et al, 2012;Lehning et al, 2000;Ling, 1995;Lu et al, 2005;Luckner & Zanke, 2007;Recking, 2009;Rousar et al, 2016;Schmidt, 1980;Shao & Lu, 2000;Vollmer & Kleinhans, 2007;Ward, 1969;Wiberg & Smith, 1987;White, 1940;Wu & Chou, 2003). Many of these models have been proposed to reproduce the Shields diagram, which displays two kinds of fluvial thresholds: a threshold obtained from extrapolating measurements of the transport rate to (nearly) vanishing transport and visual measurements of the initiation threshold of individual transport (see section 4.3 for details).…”
Section: Comparison With Previous Threshold Models 441 Mean Flow Ementioning
confidence: 99%
“…The former criteria are typically used for turbulent fluvial flows (Buffington & Montgomery, 1997;Miller et al, 1977;Paphitis, 2001, and references therein), whereas the latter criteria are preferred for laminar fluvial (Govers, 1987;Yalin & Karahan, 1979) and turbulent aeolian flows (Bagnold, 1936(Bagnold, , 1937(Bagnold, , 1941Burr et al, 2015;Carneiro et al, 2015;Chepil, 1945;Dong et al, 2003;Greeley et al, 1976;Iversen et al, 1976;Iversen & Rasmussen, 1994;Iversen & White, 1982;Lyles & Krauss, 1971;Webb et al, 2016) because bulk transport can be easily visually identified in these environments: by the formation of grain carpets in laminar fluvial flows and by very large particle hops in turbulent aeolian flows. A further situation sometimes studied in the laboratory is the beginning motion of a single particle on top of a prearranged substrate (Agudo et al, 2014(Agudo et al, , 2017(Agudo et al, , 2018Agudo & Wierschem, 2012;Celik et al, 2010;Charru et al, 2007;Deskos & Diplas, 2018;Diplas et al, 2008;Fenton & Abbott, 1977;Kudrolli et al, 2016;Valyrakis et al, 2010Valyrakis et al, , 2011Valyrakis et al, , 2013. Moreover, it is worth highlighting that Salevan et al (2017) proposed a fundamentally different criterion for the onset of significant motion based on analyzing the particle velocity distribution of all particles, including those nearly static ones that belong to the bed surface.…”
Section: Introductionmentioning
confidence: 99%